HUBUNGAN MINAT BACA DENGAN KETERAMPILAN BERBICARA SISWA SD DI GUGUS 1 MASBAGIK UTARA - Lalu Yobi Arden Wardana; Sudirman Sudirman; Heri Setiawan (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2021)
This research aims to determine whether or not there is a positive relationship between reading interests and the speaking skills of elementary school students in Cluster 1 North Masbagik. This research uses a quantitative approach with the Ex-Post facto method. This type of research is correlation. The population in this study was 158 elementary school students. Sampling technique using purposive sample with a sample number of 72 students. The data collection techniques in this study used questionnaires and oral tests. The data analysis technique used is a simple correlation with pearson product moment correlation. Hypothetical test results show sig values. (2-tailed) students' reading interests and speaking skills are worth equal to 0.000 at a rate of significance of 5% with the amount of N=72. Sig value. (2-tailed) indicates that there is a postive relationship between reading interests and the speaking skills of elementary school students in Cluster 1 North Masbagik